2017 5th IEEE International Conference on Models and Technologies for Intelligent Transportation Systems (MT-ITS) 2017
DOI: 10.1109/mtits.2017.8005632
|View full text |Cite
|
Sign up to set email alerts
|

Bus dispatching irregularity and travel time dispersion

Abstract: Service reliability is one of the most important determinants for shifting people to public transport. In low-frequency services, the reliability is considered in terms of punctuality, which becomes significant also from the standpoint of operators, given that punctuality indicators are generally included in business models. As a support for further improvement in bus punctuality in the urban area of Rome, analyses were carried out using automatic vehicle location (AVL) data of a bus line with services mixed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Finally, it has also been found that infrequent stop activity such as the operation of lifts increases headway variability as well (Albright & Figliozzi, 2012;El-Geneidy et al, 2011). (v) Traffic conditions and right of way: Congestion and incidents are one of the sources of travel time variability (Comi, Nuzzolo, Brinchi, & Verghini, 2017) and bunching (Byon et al, 2018). As travel time variability increases, headway variability is expected to increase as well.…”
Section: Determinants Of Headway Variabilitymentioning
confidence: 99%
“…Finally, it has also been found that infrequent stop activity such as the operation of lifts increases headway variability as well (Albright & Figliozzi, 2012;El-Geneidy et al, 2011). (v) Traffic conditions and right of way: Congestion and incidents are one of the sources of travel time variability (Comi, Nuzzolo, Brinchi, & Verghini, 2017) and bunching (Byon et al, 2018). As travel time variability increases, headway variability is expected to increase as well.…”
Section: Determinants Of Headway Variabilitymentioning
confidence: 99%
“…Therefore, to improve the quality of public transport services it is necessary to focus on the following problem -how to accurately determine the travel time or dwelling time of buses. Determining bus travel time in real time has many advantages, including passenger planning [12][13][14][15][16][17], where trips are planned by calculating the duration of the trip to each destination and optimizing the route [18]. With this information system operators can design and adjust the data according to the estimated duration of the trip.…”
Section: Research Statementmentioning
confidence: 99%
“…On the buses travel time is influenced by various factors such as different weather conditions [11][12], time changes of peak and non-peak hours [6,[13][14][15], information about boarding passengers [3,11,16], traffic conditions in the mode real time [17][18]. Compared to the model based on GPS data, forecasting accuracy is improved by entering speed data and passenger data during rush hours on weekdays.…”
Section: Research Statementmentioning
confidence: 99%
“…Widening the discourse, analogous considerations hold for schedule-based bus operations, where a service is often considered on time if "it runs between a certain amount of minutes early and minutes late" [16], and punctuality is usually measured at the origin and at several stops along the route, in particular, at "regulation stops" [17], i.e., key stops along the route. Suitable punctuality indicators are defined for business models purposes [18], and a bonus/penalty system can be established [17] based on whether operators exceed or fall short of a pre-defined standard.…”
Section: Introductionmentioning
confidence: 99%